Effects of surface compliance on the dynamic response and strains sustained by a player's helmeted head during ice hockey impacts. (March 2020) - de Grau, Santiago; Post, Andrew; Hoshizaki, T Blaine; Gilchrist, Michael D
In hockey, players experience different compliances during impacts to the head, from stiff ice to compliant collisions against other players. The objective of this study was to examine the effect of striking compliance in ice hockey impacts and its influence on dynamic response and brain tissue strain. Three striking caps of low, medium, and high compliances were used to impact a helmeted 50th-percentile Hybrid III headform. The headform was impacted at five locations at three velocities, representative of collision scenarios in hockey. The dependent variables, peak resultant linear and rotational acceleration as well as maximum principal strain were analyzed using a multivariate analysis of variance to determine significant differences between the compliances. The results indicated a significant effect of compliance on the responses of the headform. As expected, low-impact compliance resulted in higher linear and rotational accelerations when compared to the medium and high compliance conditions. However, while the linear and rotational acceleration responses of the medium and high compliance conditions would indicate a low chance of brain injury, the maximum principal strain magnitudes indicated a high likelihood of concussion. Medium- and high-impact compliances are a factor that has not been considered when designing and testing helmet technology in sport, with current methods reflective of low compliance surfaces, that is, those with high stiffness and rigidity. The results of this study demonstrate that an impact compliance is an important factor in producing brain injury and should be considered when certifying helmets through standard testing to mitigate the risk of brain injury.